2021
DOI: 10.1158/1078-0432.ccr-20-3724
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA Damage Repair Functions of Two Histone Deacetylases, HDAC8 and SIRT6, Sensitizes Acute Myeloid Leukemia to NAMPT Inhibition

Abstract: Purpose: Nicotinamide phosphoribosyltransferase (NAMPT) inhibitors (NAMPTi) are currently in development, but may be limited as single-agent therapy due to compound-specific toxicity and cancer metabolic plasticity allowing resistance development. To potentially lower the doses of NAMPTis required for therapeutic benefit against acute myeloid leukemia (AML), we performed a genome-wide CRISPRi screen to identify rational disease-specific partners for a novel NAMPTi, KPT-9274. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…It has currently emerged as a promising therapeutic strategy for cancer therapy. Indeed, HDAC inhibitors have shown an ability to induce differentiation and apoptosis in AML ( San José-Enériz et al, 2019 ; Zhang et al, 2021 ), leading to a good alternative for treatment, especially for those AML patients not suitable for intensive chemotherapy ( Lübbert et al, 2020 ). Here, we reported that chidamide, a selective HDAC10 inhibitor, combined with FLT3 inhibitors or traditional chemotherapy drugs showed a synergic effect on apoptosis enhancement in the acquired resistant FLT3-ITD + AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has currently emerged as a promising therapeutic strategy for cancer therapy. Indeed, HDAC inhibitors have shown an ability to induce differentiation and apoptosis in AML ( San José-Enériz et al, 2019 ; Zhang et al, 2021 ), leading to a good alternative for treatment, especially for those AML patients not suitable for intensive chemotherapy ( Lübbert et al, 2020 ). Here, we reported that chidamide, a selective HDAC10 inhibitor, combined with FLT3 inhibitors or traditional chemotherapy drugs showed a synergic effect on apoptosis enhancement in the acquired resistant FLT3-ITD + AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are many combined treatment strategies for synthetic lethality, and we have selected several representative examples for discussion and summary in Table 15 . 442 444 …”
Section: Combination Therapy Of Targeted Small-molecule Compounds In ...mentioning
confidence: 99%
“…ACY-241, a second-generation HDAC6 selective inhibitor, has been studied in combination with various agents in multiple cancers such as paclitaxel in solid tumor models; anti-PD-L1, pomalidomide, and daratumumab in multiple myeloma (MM); JQ1 in head and neck cancer; nivolumab in advanced non-small cell lung cancer; and erlotinib in pancreatic cancer [ 18 , 19 , 20 , 21 , 22 , 23 , 55 ]. On the other hand, the HDAC8 selective inhibitor, PCI-34051, has been shown to be effective when treated with KPT-2974 or cytarabine in acute myeloid leukemia and crizotinib or retinoic acid in neuroblastoma [ 56 , 57 , 58 , 59 ]. Although various studies have revealed synergistic anti-cancer effects when using HDACis with chemotherapeutic agents, therapeutic strategies targeting two epigenetic modulators have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%